Rekayasa Ulang Sistem Pembayaran Bimbingan Belajar Menggunakan Business Process Reengineering - Hari Lugis Purwanto; Kurriawan Budi Pranata (LPPM UBHINUS MALANG, 2023)
The payment system at the Smartindo Tutoring Institute. Although it has used a web-based system that is integrated with the academic system, the existing system has not been able to run properly. So, it is forced to make adjustments in the business processes of payment section. System changes are carried out using the BPR (Business Process Reengineering) method so that the system change process can be in accordance with the needs and is able to transform conventional systems into digital systems by reducing unnecessary steps. The aim of this research is to produce a new payment system based on process optimization using the BPR method. There are 4 stages of BPR that will be carried out in this research including identify processes, review update analyze as-is, design to-be, test & implement to-be. The results of these system changes resulted in a new system that showed a better level of throughput efficiency. The old system has been identified only has a throughput efficiency value of 48.39%. After analyzing and making changes to the process, the new system produces a better level of efficiency, reaching 100%. The results of better efficiency cannot be separated from the success in reducing the stages that are considered no longer needed in the workflow of the new payment system.